Associations of neonicotinoids with insulin and glucose homeostasis parameters in US adults: NHANES 2015–2016. (January 2022) - Vuong, Ann M.; Zhang, Cai; Chen, Aimin
Abstract: Neonicotinoids are replacement insecticides increasingly used for organophosphates, methylcarbamates, and pyrethroids. Experimental evidence suggests neonicotinoids may affect glucose metabolism and insulin secretion through pancreatic β cell dysfunction, oxidative stress, and inflammation. However, no epidemiologic study has investigated neonicotinoids as potential diabetogens. We examined associations between neonicotinoids with insulin and glucose homeostasis parameters among 1381 non-diabetic adults in the National Health and Nutrition Examination Survey (2015–2016). Urinary concentrations of acetamiprid, clothianidin, imidacloprid, N-desmethyl-acetamiprid, and 5-hydroxy-imidacloprid were quantified. Fasting plasma glucose, insulin, and hemoglobin A1c (HbA1c ) were assessed. Insulin resistance was defined as a homeostatic model assessment of insulin resistance ≥2.5. We used weighted linear and logistic regression to estimate associations between detectable neonicotinoids with insulin and glucose homeostasis parameters compared to non-detectable neonicotinoid concentrations. Weighted detection frequencies for imidacloprid, 5-hydroxy-imidacloprid, and N-desmethyl-acetamiprid were 4.4 %, 21.5 %, and 32.8 %, respectively. Detectable imidacloprid (β = −4.7 μIU/mL, 95 % confidence interval [CI] -8.5, −0.8) and 5-hydroxy-imidacloprid (β = −2.4 μIU/mL, 95 % CI -4.6, −0.2) were associated with lower fasting plasma insulin levels. Individuals with detectable 5-hydroxy-imidacloprid had lower odds of insulin resistance (odds ratio [OR] = 0.3, 95 % CI 0.2, 0.7). We observed evidence of sexually dimorphic associations between N-desmethyl-acetamiprid with glucose (pint  = 0.079) and 5-hydroxy-imidacloprid with HbA1c (pint  = 0.038), with patterns suggesting positive associations in males and negative associations in females. Associations between 5-hydroxy-imidacloprid and insulin were modified by body mass index (BMI) (pint  = 0.013). We additionally observed age modified associations between 5-hydyroxy-imidacloprid and glucose (pint  = 0.048). Results suggest neonicotinoids may be associated with insulin and glucose homeostasis indices and call for prospective studies to examine the metabolic impact of these replacement insecticides in humans. Highlights: We examined detectable neonicotinoids with insulin and glucose homeostasis parameters. Detectable imidacloprid and 5-hydroxy-imidacloprid were associated with lower insulin. Sex modified the relationship between N-desmethyl-acetamiprid with glucose and 5-hydroxy-imidacloprid with HbA1c. 5-hydroxy-imidacloprid was inversely associated with insulin among overweight/obese individuals.